2010
DOI: 10.1161/atvbaha.110.207977
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl Ester Transfer Protein Polymorphism (TaqIB) Associates With Risk in Postinfarction Patients With High C-Reactive Protein and High-Density Lipoprotein Cholesterol Levels

Abstract: Objective To investigate roles of inflammation and a cholesteryl ester transfer protein (CETP) polymorphism potentially related to recent findings demonstrating coronary risk with increasing HDL cholesterol (HDL-C). Methods and Results A novel graphical exploratory data analysis tool allowed examination of coronary risk in postinfarction patients relating to HDL-C and C-reactive protein (CRP). Results demonstrated a high-risk subgroup defined by high HDL-C and CRP exhibiting larger HDL particles and lower li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 34 publications
(52 reference statements)
4
43
0
1
Order By: Relevance
“…Although CETP activity was not measured, this would suggest that cholesteryl ester transfer from HDL toward apoB-containing lipoproteins is impaired consequent to lower CETP action. Altogether, the data provided in this article 11 agree with the hypothesis that dysfunctional HDL (probed by a proinflammatory state [high CRP and serum amyloid A levels] combined with high HDL cholesterol) increases the risk of recurrent CVD. Variation in the CETP gene, which is associated with lower CETP mass and activity, may contribute to recurrent risk, possibly via abnormal HDL remodeling and impairment of HDL's antiinflammatory properties.…”
Section: See Accompanying Article On Page 1657supporting
confidence: 86%
See 3 more Smart Citations
“…Although CETP activity was not measured, this would suggest that cholesteryl ester transfer from HDL toward apoB-containing lipoproteins is impaired consequent to lower CETP action. Altogether, the data provided in this article 11 agree with the hypothesis that dysfunctional HDL (probed by a proinflammatory state [high CRP and serum amyloid A levels] combined with high HDL cholesterol) increases the risk of recurrent CVD. Variation in the CETP gene, which is associated with lower CETP mass and activity, may contribute to recurrent risk, possibly via abnormal HDL remodeling and impairment of HDL's antiinflammatory properties.…”
Section: See Accompanying Article On Page 1657supporting
confidence: 86%
“…11 Among 767 nondiabetic subjects (77% male and 79% white), a high-risk subgroup (nϭ166, 56% male) was identified (recurrence rate 23.5% during a mean follow-up period of 26 months versus 13.8% in the background population). Besides 29% higher HDL cholesterol and 3-fold higher CRP levels, the high-risk subgroup individuals were also characterized by larger HDL particles, higher apolipoprotein (apo)A-I and serum amyloid A levels.…”
Section: See Accompanying Article On Page 1657mentioning
confidence: 99%
See 2 more Smart Citations
“…A series of recent investigations have indicated that there are certain instances where elevated levels of serum HDL-C are not only not associated with improved outcomes, but paradoxically increased risk of CV and all-cause mortality. These include patients with inflammation, polymorphisms in certain genes (such as CETP, lipoprotein lipase, hepatic lipase and scavenger receptor B-I), end stage renal disease (ESRD), diabetes, and coronary artery disease (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%